Pengembangan DIBSI (Digital Book IPS Berbasis Social Inquiry) untuk Siswa Kelas IV Sekolah Dasar - Sakuro, Akbar; Taofik; Nidya Chandra Muji Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop DIBSI (Social Inquiry-Based Social Studies Digital Book) for fourth-grade elementary school students and examine its feasibility as an instructional medium. The research was motivated by the limited use of interactive and contextual teaching materials in social studies learning, resulting in low student engagement. This study employed a Research and Development (R&D) method using the 4D model: define, design, development, and disseminate. Data were collected through observations, interviews, questionnaires, expert validations, and student trials. The findings showed that DIBSI was categorized as highly feasible based on expert validation and field trial results. The digital book integrates multimedia features, interactive activities, digital worksheets, quizzes, and educational games that support the Social Inquiry process. Furthermore, DIBSI improved students’ motivation, participation, conceptual understanding, and critical thinking skills in social studies learning. Therefore, DIBSI can serve as an innovative and effective digital instructional material for elementary social studies education.